Condensation of rye chromatin in somatic interphase nuclei of Ph1 and ph1b wheat - Kopecky, D; Allen, D C; Duchoslav, M; Dolezel, J; Lukaszewski, A J (Cytogenetic and genome research, 2007)
The Ph1 locus in hexaploid wheat (Triticum aestivum L.) enforces diploid-like behavior in the first metaphase of meiosis. To test the hypothesis that this chromosome pairing control is exercised by affecting the degree of chromatin condensation, the dispersion of rye chromatin in interphase nuclei in somatic tissues of wheat-rye chromosome translocations 1RS.1BL, 2RS.2BL, 2BS.2RL, 3RS.3DL and 5RS.5BL was compared in Ph1 and ph1b isogenic backgrounds. No significant differences in rye chromatin condensation that could be attributed to the Ph1 locus were detected. Regardless of the Ph1 status, each rye chromosome arm tested conformed to the general Rabl's orientation and occupied portions of the nuclei proportional to their length. Earlier observations that indicated the involvement of Ph1 locus in rye chromatin condensation in wheat could have been due either to specific loci on the studied 5RL rye arm that control the chromosome condensation process or to damage to the genetic system controlling chromatin condensation in the existing ph1b stocks of wheat. That damage might have been caused by homoeologous recombination and uneven disjunction of chromosomes from multivalents.
Keywords: chromatin; Triticum; interfáze; Chromatin; In Situ Hybridization, Fluorescence; Genes, Plant; Mitosis; mitóza; rostlinné geny; pšenice; Secale; Genome, Plant; genom rostlinný; buněčné jádro; Cell Nucleus; Interphase; hybridizace in situ fluorescenční; žito